Genetics Behind Mood Disorders: Unraveling the Genetic Complexity of Mood Disorders (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The principal goal of this paper will be tosurvey functionally relevant candidate genes for mood disorders and riskvariants revealed from the first GWA studies in clinical cohorts for mooddisorders. One is that rare variants play a more important role in theaetiology of mood disorders than previously thought and these variants might bedistinct in different populations and families. That might also explain thehuge variety and expansion of linkage peaks throughout the genome in thetraditional linkage studies. Another possibility is that the heterogeneity ofthe genetic component contributes to the aetiology of mood disorders, evenwithin one predisposing gene. While all of these can be true, the mostplausible explanation is that the phenotypes of MDD and BD are too broad, whichleads to the confounding results seen in genetic studies, since the differentaspects of broad mood disorder phenotypes are affected by distinct geneticsusceptibility genes. Thus, analysis of huge sets of genotyped individuals infuture GWA studies might not necessarily lead to the discovery of the missingheritability, but instead to discovery of new low risk alleles. They willdefinitely reveal important etiological factors for the disease and might helpto develop new, more efficient drugs, but they will not tell the whole story ofgenetics behind mood disorders.